Green Supply Chain Management Performance Measurement Using the Balanced Scorecard - Analytic Network Process in the Fresh Dairy Industry - Furqon, Chairul; Sultan, Mokh Adib; Yuin, Hwang Wu; Hendrayati, Heny; A, Ahmad Paris (Politeknik APP Jakarta, 2022)
The objective of this study was to obtain an overview of the process and measure the performance of Green Supply Chain Management in the dairy industry in Bandung area, West Java, Indonesia. The method used in this research is the Balanced Scorecard - Analytic Network Process to measure the performance of Green Supply Chain Management. Data was collected through the observation, in-depth interviews, questionnaires, and literature studies. The research findings show that some Key Performance Indicators has not been achieved the target, and must be improved to optimize the overall Green Supply Chain Management. The novelty of this research concerning to the importance of business organizations paying attention on Green Supply Chain Management for the long term. The open market for the domestic fresh milk industry is very vulnerable to threats due to environmental issues. Therefore, the results of this study are expected to be a reference for other business organizations.